Detection and Control of Pantoea agglomerans Causing Plum Bacterial Shot-Hole Disease by Loop-Mediated Isothermal Amplification Technique - Shu, Ran; Yin, Xianhui; Long, Youhua; Yuan, Jun; Zhou, Houyin (Frontiers in Microbiology, 2022)
Plum bacterial shot-hole caused by Pantoea agglomerans is one of the primary bacterial diseases in plum tree planting areas, resulting in abnormal growth of plum trees and severe economic losses. Early diagnosis of P. agglomerans is crutial to effectively control plant diseases. In this study, loop-mediated isothermal amplification (LAMP) analysis for genome-specific gene sequences was developed for the specific detection of P. agglomerans. We designed the LAMP primers based on the gyrB gene of P. agglomerans. The best reaction system was 0.2 μmol·L-1 for outer primer F3/B3 and 1.6 μmol·L-1 for inner primer FIP/BIP. The LAMP reaction was optimal at 65℃ for 60 min based on the colour change and gel electrophoresis. This technology distinguished P. agglomerans from other control bacteria. The detection limit of the LAMP technology was 5 fg·μL-1 genomic DNA of P. agglomerans, which is 1000 times that of the traditional PCR detection method. The LAMP technology could effectively detect the DNA of P. agglomerans from the infected leaves without symptoms after indoor inoculation. Furthermore, the LAMP technology was successfully applied to detect field samples, and the field control effect of 0.3% tetramycin after LAMP detection reached 82.51%, which was 7.90% higher than that of conventional control. The proposed LAMP detection technology in this study offers the advantages of ease of operation, visibility of results, rapidity, accuracy and high sensitivity, making it suitable for the early diagnosis of plum bacteria shot-hole disease.